Atividade ascorbato peroxidase e haloperoxidase de agentes terapêuticos redox-ativos à base de metaloporfirinas hidrossolúveis - Sampaio, Rômulo Severo (2019)
The study’s main purpose has been to verify the behavior of different metalloporphyrins, typically used as redox-active therapeutic agents, in different systems of biological interest. The initial studies allowed to assess the efficiency of 14 water-soluble manganese metalloporphyrins (MnPs) in catalyzing the ascorbate oxidation reaction, where it was possible to determine the initial rates (v0(Asc)ox and v0(O2)red) for the catalysis of ascorbate oxidation reaction in two different media (Tris and phosphate buffers) using spectrophotometric and electrochemical measurements. The compound named as MnTM-2- PyP5+ was the most efficient for both evaluated buffers. The data showed that the initial rates are related to the reduction potential (E1/2). This relationship showed a bell-shaped trend, with catalytic activity increasing from negative potentials ~ -200 mV vs NHE, and with optimum potentials ranging from ~ +50 mV to ~ +300 mV vs NHE. The catalytic reaction kinetics of the MnP/ascorbate system in the two buffers was influenced by the hydrogen bonding capacity between the buffer and the MnP. Furthermore, it was also sought to evaluate the haloperoxidase activity of nine MnPs, typically involved in oxidative stress redox modulation studies, using the classical spectrophotometric monochlorodimedone (MCD) halogenation assay. The results have demonstrated the ability of nine metalloporphyrins to catalyze the halogenation reaction of MCD, therefore, such compounds showed haloperoxidase activity. This study was able to determine the initial rates for catalysis of MCD halogenation reactions in phosphate buffer using spectrophotometric measurements. Data analyses have demonstrated that the initial rates and, consequently, the MnPs’ apparent rates (kobs) are related to E1/2 and also to the steric effect of the porphyrin pyridine ringside chains. This relationship did not show a clear tendency for both halogenation types (bromination and chlorination). Nonetheless, it was concluded that MnPs are more efficient for bromination reactions, and that they have catalytic activity with optimum potentials ranging from ~ +220 mV to ~ +240 mV vs NHE, for both halogenation types. The most efficient compounds for catalytic halogenation of MCD were MnTM-2-PyP5+ for both bromination and chlorination reactions, together with MnTM-3-PyP5+ for bromination reactions only. In an additional part of this work, it was pursued to analyze and quantify Mn (III) and Fe (III) metalloporphyrins in mammalian plasma and organs by LC-MS/MS in biological samples.